LANGUAGE INTERFERENCE AND LANGUAGE INTEGRATION: A SOCIOLINGUISTIC STUDY OF STUDENTS AT THE ISLAMIC UNIVERSITY OF IBRAHIMY BANYUWANGI - Nurul Fatimah; Eka Ramiati (International Conference on Humanity Education and Society (ICHES), 2026)
The two linguistic phenomena in bilingual societies, namely interference and integration, are interesting topics to examine, as both commonly occur in everyday language use. These phenomena arise due to contact between two languages, namely the first language and the second language. This study aims to objectively describe the phenomena of language interference and integration from a sociolinguistic perspective among students of Ibrahimy Islamic University, Banyuwangi. This research employed aqualitative approach with a phenomenological research design. Data were collected using observation and note-taking techniques, then analyzed inductively and subsequently generalized to obtain the research findings. Data validity was ensured through data triangulation. The results of the analysis indicate that language interference occurs at the phonological and morphological levels. Phonological interference manifests in four forms: monophthongization, vowel modification, apocope, and syncope. Meanwhile, morphological interference from Javanese into Indonesian includes four aspects: (1) the prefix (N-) with allomorphs (ny-), (ng-), and (n-); (2) the suffix ( e); (3) the circumfix (ke-an); and (4) reduplication (full reduplication and reduplication with sound variation). In contrast, the phenomenon of language integration occurs at the level of loanwords from Javanese into Indonesian through both adaptation and adoption processes.